2021
DOI: 10.1016/j.ssmph.2021.100771
|View full text |Cite
|
Sign up to set email alerts
|

Social status differences in allostatic load among young adults in the United States

Abstract: Allostatic load refers to wear and tear on the body due to repeated activation of the stress response and, thus, may be an early subclinical indicator of future disease and mortality risk. To date, few studies of allostatic load have focused on young adults, racial/ethnic comparisons that include Mexican Americans, or the interplay between race/ethnicity, gender, and educational attainment. To fill these gaps, we used data on non-Hispanic Black, non-Hispanic White, and Mexican-origin respondents from Waves I (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Although education – either measured as years of schooling or duration in school – attenuated Black-White inequities in allostatic load, only duration in school reduced race inequities in allostatic load to statistical non-significance in linear regression models. Studies focused on understanding Black-White inequities in allostatic load often adjust for educational attainment to account for confounding or to estimate mediation; however, educational attainment often explains little of the race inequity in allostatic load ( Mitchell et al, 2020 ; Moore et al, 2021 ; Richardson et al, 2021 ). This may be due to the use of an imprecise measure that ignores systemic structural racism in the education system ( Walsemann et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although education – either measured as years of schooling or duration in school – attenuated Black-White inequities in allostatic load, only duration in school reduced race inequities in allostatic load to statistical non-significance in linear regression models. Studies focused on understanding Black-White inequities in allostatic load often adjust for educational attainment to account for confounding or to estimate mediation; however, educational attainment often explains little of the race inequity in allostatic load ( Mitchell et al, 2020 ; Moore et al, 2021 ; Richardson et al, 2021 ). This may be due to the use of an imprecise measure that ignores systemic structural racism in the education system ( Walsemann et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may also reflect the historically contingent and cohort dependent nature of education as an explanation for Black-White inequities in allostatic load. Several studies have found that, among Black men and/or women, education has a positive association with allostatic load, such that post-secondary schooling is related to higher allostatic load ( Howard & Sparks, 2015 ; Richardson et al, 2021 ; Sims & Coley, 2019 ). Yet, we found no evidence that the education—allostatic load relationship differed by race.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem of single axis identity analysis underscores why intersectional research on Black women (the nexus of subordinated race and gender identities) is necessary. Correspondingly, an analysis of data from the National Longitudinal Study of Adolescent to Adult Health found that completion of higher education was no more or less protective for AL in Black women [ 14 ]. While methodological and technical limitations introduce difficulty in correlating perceived stress with adverse AL, there is an urgent need to explore the impact of social stressors on Black women in association with their educational achievement.…”
Section: Introductionmentioning
confidence: 99%